2.6k views
1 vote
Can someone please help me?

Can someone please help me?-example-1
User Ach
by
4.8k points

1 Answer

4 votes

Answer:

( - 1 , - 1 )

Option D is the correct option.

Explanation:

y = - 2x - 3 → Equation ( i )

y = 3x + 2 → Equation ( ii )

Using elimination method

y + 2x = - 3

y - 3x = 2

---------------------

5x = - 5

Divide both sides of the equation by 5


(5x)/(5) = ( - 5)/(5)

Calculate


x = - 1

Again, Putting the value of x in equation ( ii ) in order t get the value of y


y = 3x + 2

plug the value of x


= 3 * ( - 1) + 2

Any expression multiplied by ( - 1 ) equals it's opposite


= - 3 + 2

Calculate


= - 1

Therefore, The possible solution of the system is the ordered pair ( x , y )


(x \:, y \: ) = ( - 1 \:, - 1)

-----------------------------------------------------------------------

Check if the given ordered pair is the solution of the system of equation


- 1 = - 2 * ( - 1) - 3


- 1 = 3 * ( - 1) + 2

Simplify the equation


- 1 = - 1


- 1 = - 1

Since all the equalities are true, the ordered pair is the solution of the system.

( x , y ) = ( - 1 , - 1 )

Hope this helps..

Best regards!!

User MikeHelland
by
5.4k points